A gradient cooling rate field controlled heat treatment process suitable for TC18 tube piercing
Patent Information
- Application Number
- CN202510513694.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-23
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2045-04-23
AI Technical Summary
该工艺采用β单相区固溶结合梯度冷速域控的组织优化方法,实现了β晶粒均匀化与α相多尺度组织重构,提升了TC18管材的强塑性匹配关系,突破性提升了TC18穿轧管材的综合力学性能与工程适用性,解决了现有热处理工艺存在的组织适配性局限、精确调控冷速缺失、效率低能耗高、适配量产能力不足等瓶颈问题
[0024]1、本发明采用β单相区固溶+高温快速控冷+低温窄域控冷的热处理工艺,通过精准控制梯度冷速域控的温度及冷速,高效地实现了穿轧态管材β晶粒的均匀化重构及多尺度α相异构组织调控,获得β晶粒均匀且包含微米级粗大α相和纳米级细小α相的多尺度异构组织,在保证TC18管材强度的同时提高了TC18管材的塑性,提升了TC18管材的强塑性匹配关系,为航空航天薄壁构件及深海装备的使用寿命提升提供关键技术支撑。
Smart Images

Figure CN120249857B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of titanium alloy heat treatment technology, specifically relating to a gradient cooling rate controlled heat treatment process suitable for TC18 pierced rolled tubes. Background Technology
[0002] TC18 tubing, as a core component in the field of advanced structural materials, has become a key material carrier for high-end manufacturing in aerospace, deep-sea equipment, and hydrogen energy storage and transportation due to its high specific strength, excellent plasticity, and outstanding corrosion resistance. In industrial manufacturing, piercing rolling technology, with its near-net-shape forming capability and high material utilization, has become the core process for achieving high-precision, low-cost, and mass production of TC18 titanium tubing. However, the inherent characteristic of this process—multiple passes of intense local deformation above the β-phase transformation point—leads to a significant non-uniform grain size distribution in the tubing: the average size of large-scale grains is approximately 200 μm, while the average size of small-scale grains is approximately 20 μm. Furthermore, at the microscopic level, the imbalance of dynamic phase transformation kinetics induces abnormal enrichment of the secondary α-phase (volume fraction greater than 75%), forming submicron-scale needle-like morphologies (average length less than 1 μm). This "non-uniform grain size + ultra-refined α-phase" piercing-rolled microstructure characteristic causes the material's yield strength to exceed 1300 MPa while the elongation drops sharply to below 3%, forming a typical strength-plasticity inversion effect. Therefore, while ensuring the strength of TC18 rolled tubing, improving the alloy's plasticity is an urgent problem to be solved.
[0003] Existing research indicates that α / β phase parameters (including α phase size, volume fraction, distribution morphology, and β grain size) are the main factors affecting the mechanical properties of titanium alloys. Specifically, fine acicular α phases significantly improve alloy strength through a strong pinning effect on dislocations; while coarse lamellar or spherical α phases are more conducive to improving plasticity through crack propagation inhibition mechanisms. Based on this, related research has optimized the performance of TC18 alloy through different heat treatment paths: Patent CN115725916B uses a single-stage solution aging process to control the size of the α precipitate phase (5μm~0.2μm), enabling the forged TC18 alloy to achieve a strong-plasticity balance with a tensile strength of 1108MPa and an elongation of 9%; Patent CN115976441B constructs a dual-state microstructure containing spherical primary α phase and acicular secondary α phase through solution treatment and multi-step aging, enabling the tensile strength of the forged TC18 alloy to exceed 1400MPa, but the elongation drops below 5%; Patent CN118186325B uses a four-stage multi-annealing process to synergistically control the size of the grain boundary α phase and β grains, ultimately achieving a comprehensive improvement in tensile strength of 1110MPa~1140MPa and elongation of 11%~14% for the forged TC18 alloy. However, the above methods have significant limitations in the engineering application of pierced-rolled tubes:
[0004] ①Limitations in microstructure adaptability: Existing heat treatment processes are all based on forged microstructure and cannot effectively control the rolled microstructure formed by processing above the β phase transformation point;
[0005] ② Production efficiency bottleneck: Stepped process parameters (such as CN115976441B which uses two aging temperatures) significantly reduce the production line cycle time, making it difficult to adapt to the large-scale production needs of thread-rolled pipes.
[0006] ③Soaring energy costs: Complex multi-stage heat treatment (such as CN118186325B multiple annealing which requires 4 temperature control conversions) leads to an increase in energy costs of more than 40%, significantly deteriorating economic efficiency;
[0007] ④ Lack of precise cooling rate control: Existing process systems overemphasize the optimization of time-temperature parameters (such as aging temperature gradient design and holding time control), but simply categorize the cooling rate as a process connection step, failing to achieve microstructure control by precisely changing the cooling rate; in addition, random fluctuations in a wide range of cooling rates (such as the cooling rate range of 1 min / s to 20 min / s in the first stage of CN118186325B) can easily lead to a significant increase in the size dispersion of the α phase, thereby inducing abnormal fluctuations in strength-plasticity matching. Summary of the Invention
[0008] The technical problem to be solved by this invention is to provide a gradient cooling rate controlled heat treatment process suitable for TC18 pierced-rolled tubes, addressing the shortcomings of the prior art. This process employs a microstructure optimization method combining β single-phase region solid solution treatment with gradient cooling rate controlled cooling, achieving β grain homogenization and α phase multi-scale microstructure reconstruction. This improves the strength-plasticity matching relationship of TC18 tubes, significantly enhancing the comprehensive mechanical properties and engineering applicability of TC18 pierced-rolled tubes. It solves the bottleneck problems of existing heat treatment processes, such as limited microstructure adaptability, lack of precise cooling rate control, low efficiency and high energy consumption, and insufficient adaptability for mass production.
[0009] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is: a gradient cooling rate controlled heat treatment process suitable for TC18 pierced rolling tubes, characterized in that the process includes the following steps:
[0010] Step 1, β-single-phase solution treatment: Place the TC18 pierced-rolled tube in a T... β The solution is then applied at the above temperature for 0.5 to 1 hour.
[0011] Step 2, Gradient Cooling Rate Control: The TC18 rolled tube after solution treatment in Step 1 is first subjected to rapid cooling in a high-temperature stage: rapidly cooled from the β phase region to T at a cooling rate of not less than 0.5℃ / s. β Next, a narrow-range controlled cooling process is performed at a low temperature: the temperature is reduced to room temperature at a cooling rate of 0.03℃ / s to 0.1℃ / s to obtain the heat-treated TC18 pierced tube.
[0012] This invention innovatively proposes a gradient cooling rate domain-controlled heat treatment process, which retains the high-precision forming advantage of TC18 through-rolled tubes and exerts a synergistic effect through "β single-phase region solid solution + high-temperature rapid controlled cooling (not less than 0.5℃ / s) + low-temperature narrow-domain controlled cooling (0.03℃ / s~0.1℃ / s)". Specifically, a short-time solid solution strategy in the β single-phase region is first adopted to suppress abnormal growth of β grains while eliminating the grain inhomogeneity of the original rolled structure in TC18 pipes through complete recrystallization of the β phase. This can typically reduce the grain size dispersion from the original ±180μm to ±30μm, significantly improving the anisotropy of the pipes. Then, a gradient cooling rate domain control process is adopted to overcome the limitations of phase transformation control in traditional constant cooling rate processes. First, rapid cooling at high temperature suppresses excessive growth and coarsening of β grains and quickly provides the driving force for α phase nucleation. Then, in the α+β two-phase region, the cooling rate-temperature-phase transformation coupling effect of narrow-domain controlled cooling at low temperature precisely controls the precipitation kinetics of the α phase. This results in a multi-scale heterogeneous structure in which micron-sized coarse α phases (10μm~22μm) and fine α phases (less than 1μm) coexist within the uniform β matrix, taking into account both dislocation pinning strengthening and crack propagation inhibition effects, thereby simultaneously improving the strength and plasticity of TC18 through-rolled pipes.
[0013] The gradient cooling rate controlled heat treatment process applicable to TC18 pierced rolled tubes is characterized in that the chemical composition of the TC18 pierced rolled tubes meets the requirements of TC18 in GB / T 3620.1-2020 "Titanium and Titanium Alloys Grades and Chemical Compositions".
[0014] The above-mentioned gradient cooling rate domain-controlled heat treatment process for TC18 pierced rolled tubes is characterized in that the initial microstructure of the TC18 pierced rolled tubes in step one is as follows: the grain size dispersion is relatively large, with the average size of large-scale grains close to 200 μm and the average size of small-scale grains close to 20 μm. The secondary α-phase anomalous enrichment integral is greater than 75%, and it exhibits a submicron needle-like morphology with an average length of less than 1 μm.
[0015] The aforementioned gradient cooling rate controlled heat treatment process for TC18 pierced rolling tubes is characterized in that the solution treatment temperature in step one is T. β Above 10℃~50℃.
[0016] The gradient cooling rate controlled heat treatment process applicable to TC18 pierced tubes described above is characterized in that the grain size dispersion of the TC18 pierced tubes after solution treatment in step one is less than ±20μm.
[0017] The gradient cooling rate controlled heat treatment process applicable to TC18 pierced tubes described above is characterized in that the fastest cooling rate in the high-temperature stage in step two is 0.5℃ / s.
[0018] The aforementioned gradient cooling rate controlled heat treatment process for TC18 pierced rolling tubes is characterized in that the final temperature of the rapid cooling in the high-temperature stage in step two is T. β The temperature range is 30℃ to 70℃. More preferably, the final temperature of the rapid cooling during the high-temperature stage is T. β Below 50℃~70℃.
[0019] Typically, the solution treatment temperature in step one of this invention corresponds to the rapid cooling endpoint temperature of the high-temperature stage described in step two, with a typical temperature difference of 80°C. For example, when the solution treatment temperature is T... β +10℃ corresponds to T β -70℃, T β +50℃ corresponds to T β -30℃, to precisely control the starting and ending temperatures of the first stage of gradient cooling rate control, namely the high-temperature stage, to ensure the uniformity of the cooling temperature range.
[0020] The gradient cooling rate controlled heat treatment process applicable to TC18 pierced tubes described above is characterized in that the cooling rate of the narrow-range controlled cooling in the low-temperature stage in step two is 0.06℃ / s to 0.1℃ / s.
[0021] The aforementioned gradient cooling rate controlled heat treatment process for TC18 pierced-rolled tubing is characterized in that the microstructure of the TC18 pierced-rolled tubing after heat treatment in step two is as follows: β grains are homogenized, grain size dispersion is less than ±30μm, and multi-scale heterogeneous microstructure is reconstructed, wherein the coarse α phase size is 10μm to 22μm, and the fine α phase size is less than 1μm. More preferably, the coarse α phase size is 10μm to 15μm.
[0022] The aforementioned gradient cooling rate controlled heat treatment process for TC18 pierced-rolled tubing is characterized in that, in step two, the TC18 pierced-rolled tubing after heat treatment has a tensile strength of 1052 MPa to 1126 MPa, a yield strength of 934 MPa to 1012 MPa, and an elongation of 13.0% to 15.6%. More preferably, the TC18 pierced-rolled tubing after heat treatment has a tensile strength of 1110 MPa to 1120 MPa, a yield strength of 991 MPa to 1004 MPa, and an elongation of 13.0% to 14.1%.
[0023] Compared with the prior art, the present invention has the following advantages:
[0024] 1. This invention employs a heat treatment process of β single-phase region solid solution + high-temperature rapid controlled cooling + low-temperature narrow-range controlled cooling. By precisely controlling the temperature and cooling rate of the gradient cooling rate domain, it efficiently achieves the homogenization and reconstruction of β grains in the rolled tube and the regulation of multi-scale α-phase heterogeneous structure. This results in a multi-scale heterogeneous structure with uniform β grains containing micron-sized coarse α phases and nano-sized fine α phases. While ensuring the strength of TC18 tube, it also improves the plasticity of TC18 tube and enhances the strength-plasticity matching relationship of TC18 tube, providing key technical support for improving the service life of aerospace thin-walled components and deep-sea equipment.
[0025] 2. The heat treatment process of this invention achieves β-grain homogenization control, eliminates local stress concentration caused by uneven grain size in the original rolled structure of TC18 pipe, improves the quality of TC18 pipe, and reconstructs multi-scale heterogeneous microstructure, achieving a comprehensive improvement in the strength and plasticity of TC18 pipe. It breaks through and increases the tensile strength of TC18 rolled pipe to 1052MPa~1126MPa, the yield strength to 934MPa~1012MPa, and the elongation to 13.0%~15.6%.
[0026] 3. The heat treatment process of this invention is simple, requiring only a single heating and continuous cooling throughout the entire process. Compared with traditional multi-stage heat treatment, it shortens the heat treatment process by more than 50%, reduces the number of equipment start-ups and shutdowns by 70%, and improves the production line processing efficiency by more than 2 times. It has the characteristics of strong engineering applicability and high precision in microstructure control, meeting the industrial needs of large-scale pierced rolling tubes. It realizes the engineering application scenario of strength-plasticity matching and can provide a reliable solution for the performance optimization of key load-bearing pipe components in the aerospace field.
[0027] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0028] Figure 1 This is the EBSD diagram of the original grain distribution of the TC18 pierced tube used in this invention.
[0029] Figure 2 This is a SEM image of the original microstructure of the TC18 pierced-rolled pipe used in this invention.
[0030] Figure 3 This is a flowchart of the gradient cooling rate controlled heat treatment process of the present invention.
[0031] Figure 4 This is a SEM image of the grain distribution of the TC18 pierced tube after solution treatment in Example 1 of the present invention.
[0032] Figure 5 This is a SEM image of the microstructure of the TC18 pierced-rolled tube after heat treatment in Embodiment 1 of the present invention.
[0033] Figure 6 This is a SEM image of the microstructure of the TC18 pierced tube after heat treatment in Embodiment 2 of the present invention.
[0034] Figure 7 This is a SEM image of the microstructure of the TC18 pierced-rolled tube after heat treatment in Embodiment 3 of the present invention.
[0035] Figure 8 This is a SEM image of the microstructure of the TC18 pierced-rolled tube after heat treatment in Example 4 of the present invention.
[0036] Figure 9 This is a SEM image of the microstructure of the TC18 pierced-rolled tube after heat treatment in Example 5 of the present invention.
[0037] Figure 10 This is a SEM image of the microstructure of the TC18 pierced-rolled pipe after single-stage aging in Comparative Example 1 of this invention.
[0038] Figure 11 This is a SEM image of the microstructure of the TC18 pierced-rolled pipe after single-stage aging in Comparative Example 2 of this invention.
[0039] Figure 12 This is a SEM image of the microstructure of the TC18 pierced-rolled pipe after single-stage aging in Comparative Example 3 of this invention. Detailed Implementation
[0040] Examples 1-5 and Comparative Examples 1-3 of this invention use TC18 titanium alloy rolled tubing with a diameter of φ102mm / 78mm as raw material. Its chemical composition is Ti-5Al-5Mo-5V-1Cr-1Fe, which meets the requirements of TC18 in GB / T3620.1-2020 "Titanium and Titanium Alloys - Grades and Chemical Compositions". The phase transformation point T... β At 830℃, its original grain distribution and original microstructure are as follows: Figures 1-2 As shown. From Figures 1-2 It can be seen that the initial microstructure of the TC18 pierced-rolled tube is as follows: (1) Uneven grain size distribution: The grain size dispersion is relatively large, with the average size of large-scale grains approaching 200 μm and the average size of small-scale grains approaching 20 μm; (2) The integral number of the secondary α-phase anomalously enriched group is greater than 75%, and it exhibits a submicron needle-like morphology with an average length of less than 1 μm. The yield strength of the TC18 pierced-rolled tube is 1300 MPa, and the elongation is 3%.
[0041] like Figure 3 As shown, the process of the gradient cooling rate domain-controlled heat treatment process of the present invention is as follows: (1) β single-phase region solid solution: in T β(1) Solution treatment is carried out at 10℃~50℃, i.e. 840℃~880℃ for 0.5h~1h to eliminate the original microstructure characteristics; (2) Gradient cooling rate control: During the high temperature stage, the solution-treated TC18 pierced pipe is rapidly cooled from the β phase region to T at a cooling rate of not less than 0.5℃ / s. β The temperature range is 30℃~70℃ (760℃~800℃), and the low-temperature stage is cooled to room temperature at a cooling rate of 0.03℃ / s~0.1℃ / s.
[0042] Example 1
[0043] This embodiment includes the following steps:
[0044] Step 1, β-single-phase solution treatment: Place the TC18 rolled pipe at 840℃ for 1 hour for solution treatment;
[0045] Step 2, Gradient Cooling Rate Control: The TC18 pierced tube after solution treatment in Step 1 is first subjected to rapid cooling in the high-temperature stage: rapidly cooled from the β phase region to 760℃ at a cooling rate of 0.5℃ / s, and then subjected to narrow-range controlled cooling in the low-temperature stage: cooled to room temperature at a cooling rate of 0.03℃ / s, to obtain the heat-treated TC18 pierced tube.
[0046] Figure 4 This is a SEM image of the grain distribution of the TC18 rolled tube after solution treatment in this embodiment. Figure 4 It can be seen that the average grain size of the TC18 pierced tube after solution treatment is 342 μm, and the grain size dispersion is ±19 μm.
[0047] Figure 5 This is a SEM image of the microstructure of the TC18 rolled tube after heat treatment in this embodiment, where region 1 represents coarse α phase and region 2 represents fine α phase. Figure 5 It can be seen that the microstructure of the heat-treated TC18 pierced tube exhibits multi-scale heterogeneous characteristics. The coarse α phase has an average size of about 22 μm and a volume fraction of about 30%, while the fine α phase has an average size of less than 1 μm and a volume fraction of about 10%.
[0048] Example 2
[0049] This embodiment includes the following steps:
[0050] Step 1, β-single-phase solution treatment: Place the TC18 rolled pipe at 840°C for 1 hour for solution treatment;
[0051] Step 2, Gradient Cooling Rate Control: The TC18 pierced tube after solution treatment in Step 1 is first subjected to rapid cooling in the high-temperature stage: rapidly cooled from the β phase region to 760℃ at a cooling rate of 0.5℃ / s, and then subjected to narrow-range controlled cooling in the low-temperature stage: cooled to room temperature at a cooling rate of 0.06℃ / s, to obtain the heat-treated TC18 pierced tube.
[0052] Figure 6 This is a SEM image of the microstructure of the TC18 rolled tube after heat treatment in this embodiment, where region 1 represents coarse α phase and region 2 represents fine α phase. Figure 6 It can be seen that the microstructure of the heat-treated TC18 pierced tube exhibits multi-scale heterogeneous characteristics. The coarse α phase has an average size of about 15 μm and a volume fraction of about 20%, while the fine α phase has an average size of less than 1 μm and a volume fraction of about 30%.
[0053] Example 3
[0054] This embodiment includes the following steps:
[0055] Step 1, β-single-phase solution treatment: Place the TC18 rolled pipe at 840℃ for 1 hour for solution treatment;
[0056] Step 2, Gradient Cooling Rate Control: The TC18 pierced tube after solution treatment in Step 1 is first subjected to rapid cooling in the high-temperature stage: rapidly cooled from the β phase region to 760℃ at a cooling rate of 0.5℃ / s, and then subjected to narrow-range controlled cooling in the low-temperature stage: cooled to room temperature at a cooling rate of 0.1℃ / s, to obtain the heat-treated TC18 pierced tube.
[0057] Figure 7 This is a SEM image of the microstructure of the TC18 rolled tube after heat treatment in this embodiment, where region 1 represents coarse α phase and region 2 represents fine α phase. Figure 7 It can be seen that the microstructure of the heat-treated TC18 pierced tube exhibits multi-scale heterogeneous characteristics. The coarse α phase has an average size of about 10 μm and a volume fraction of about 10%, while the fine α phase has an average size of less than 1 μm and a volume fraction of about 50%.
[0058] Example 4
[0059] This embodiment includes the following steps:
[0060] Step 1, β-single-phase solution treatment: Place the TC18 rolled pipe at 880℃ for 1 hour for solution treatment;
[0061] Step 2, Gradient Cooling Rate Control: The TC18 pierced tube after solution treatment in Step 1 is first subjected to rapid cooling in the high-temperature stage: rapidly cooled from the β phase region to 800℃ at a cooling rate of 0.5℃ / s, and then subjected to narrow-range controlled cooling in the low-temperature stage: cooled to room temperature at a cooling rate of 0.1℃ / s, to obtain the heat-treated TC18 pierced tube.
[0062] Figure 8 This is a SEM image of the microstructure of the TC18 rolled tube after heat treatment in this embodiment, where region 1 represents coarse α phase and region 2 represents fine α phase. Figure 8 It can be seen that the microstructure of the heat-treated TC18 pierced tube exhibits multi-scale heterogeneous characteristics. The coarse α phase has an average size of about 10 μm and a volume fraction of about 10%, while the fine α phase has an average size of less than 1 μm and a volume fraction of about 50%.
[0063] Example 5
[0064] This embodiment includes the following steps:
[0065] Step 1, β-single-phase solution treatment: The TC18 rolled pipe is placed at 880℃ for 0.5h for solution treatment;
[0066] Step 2, Gradient Cooling Rate Control: The TC18 pierced tube after solution treatment in Step 1 is first subjected to rapid cooling in the high-temperature stage: rapidly cooled from the β phase region to 800℃ at a cooling rate of 0.5℃ / s, and then subjected to narrow-range controlled cooling in the low-temperature stage: cooled to room temperature at a cooling rate of 0.03℃ / s, to obtain the heat-treated TC18 pierced tube.
[0067] Figure 9 This is a SEM image of the microstructure of the TC18 rolled tube after heat treatment in this embodiment, where region 1 represents coarse α phase and region 2 represents fine α phase. Figure 9 It can be seen that the microstructure of the heat-treated TC18 pierced tube exhibits multi-scale heterogeneous characteristics. The coarse α phase has an average size of about 22 μm and a volume fraction of about 30%, while the fine α phase has an average size of less than 1 μm and a volume fraction of about 10%.
[0068] Comparative Example 1
[0069] This comparative example includes the following steps:
[0070] Step 1, β-single-phase solution treatment: Place the TC18 rolled pipe at 840℃ for 1 hour for solution treatment;
[0071] Step 2, Single-stage aging: The TC18 pierced-rolled pipe after solution treatment in Step 1 is rapidly cooled from the β phase region to 750℃ at a cooling rate of 0.5℃ / s and held at that temperature for 3 hours for single-stage aging. It is then water-cooled to room temperature to obtain the heat-treated TC18 pierced-rolled pipe.
[0072] Figure 10 This is a SEM image of the microstructure of TC18 threaded tube after single-stage aging in this comparative example. Figure 10 It can be seen that the microstructure of the heat-treated TC18 pierced tube exhibits a homogeneous micron-sized α-precipitate, with an average α-phase size of approximately 20 μm and a volume fraction of approximately 20%.
[0073] Comparative Example 2
[0074] This comparative example includes the following steps:
[0075] Step 1, β-single-phase solution treatment: Place the TC18 rolled pipe at 840℃ for 1 hour for solution treatment;
[0076] Step 2, Single-stage aging: The TC18 pierced-rolled pipe after solution treatment in Step 1 is first subjected to rapid cooling at a high temperature stage: it is rapidly cooled from the β phase region to 650℃ at a cooling rate of 0.5℃ / s and held at that temperature for 3 hours for single-stage aging, and then water-cooled to room temperature to obtain the heat-treated TC18 pierced-rolled pipe.
[0077] Figure 11 This is a SEM image of the microstructure of TC18 threaded tube after single-stage aging in this comparative example. Figure 11 It can be seen that the microstructure of the heat-treated TC18 pierced tube exhibits a homogeneous micron-sized α-precipitate, with an average α-phase size of approximately 5 μm and a volume fraction of approximately 35%.
[0078] Comparative Example 3
[0079] This comparative example includes the following steps:
[0080] Step 1, β-single-phase solution treatment: Place the TC18 rolled pipe at 840℃ for 1 hour for solution treatment;
[0081] Step 2, Single-stage aging: The TC18 pierced-rolled pipe after solution treatment in Step 1 is first subjected to rapid cooling at a high temperature: rapidly cooled from the β phase region to 550℃ at a cooling rate of 0.5℃ / s and held at that temperature for 3 hours for single-stage aging, and then water-cooled to room temperature to obtain the heat-treated TC18 pierced-rolled pipe.
[0082] Figure 12 This is a SEM image of the microstructure of TC18 threaded tube after single-stage aging in this comparative example. Figure 12 It can be seen that the microstructure of the heat-treated TC18 pierced tube exhibits a homogeneous micron-sized α-precipitate, with an average α-phase size of less than 1 μm and a volume fraction of approximately 55%.
[0083] The room temperature mechanical properties, average grain size, and grain size dispersion of the TC18 pierced-rolled tubes after heat treatment in Examples 1-5 and Comparative Examples 1-3 of this invention are shown in Table 1 below.
[0084] Table 1
[0085]
[0086] Comparing Examples 1-5 of the present invention with Comparative Examples 1-3 reveals that the embodiments of the present invention exhibit significant advantages in terms of mechanical properties and microstructure control. Specifically, Examples 1-5 demonstrate superior strength and plasticity matching, with tensile strength (1052 MPa-1126 MPa) and yield strength (934 MPa-1012 MPa) significantly better than Comparative Example 1 (907 MPa / 854 MPa) and Comparative Example 2 (1010 MPa / 942 MPa). Simultaneously, the elongation is generally higher (13.0%-15.6%), significantly better than Comparative Example 3 (only 1.5%). This indicates that by optimizing the microstructure, the embodiments improve strength while avoiding extreme embrittlement phenomena similar to Comparative Example 3. Therefore, the fine needle-like α phase in the multi-scale heterogeneous microstructure constructed by the heat treatment process of this invention significantly improves the strength of TC18 rolled tubes through the strong pinning effect on dislocations, while the coarse lamellar α phase ensures the plasticity of TC18 rolled tubes through the crack propagation inhibition mechanism. Conversely, using only a single-stage aging heat treatment process, Comparative Example 1 has a low strength of TC18 rolled tubes due to the high volume fraction of coarse α phase (20%) and the lack of fine α phase; Comparative Example 3, which relies entirely on fine α phase (volume fraction 55%) and lacks coarse α phase, has a tensile strength as high as 1334 MPa, but the elongation drops sharply to 1.5%, reflecting the limitations of a single strengthening mechanism; although Comparative Example 2 shows a relatively good strength-plasticity match, Examples 1 to 5 of this invention all achieve a significant improvement in both strength and plasticity on the basis of this.
[0087] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention in any way. Any simple modifications, alterations, and equivalent changes made to the above embodiments based on the inventive essence shall still fall within the protection scope of the present invention.
Claims
1. A gradient cooling rate controlled heat treatment process suitable for TC18 pierced rolling tubes, characterized in that, The process includes the following steps: Step 1, β-single-phase solution treatment: Place the TC18 pierced-rolled tube in a T... β The solution treatment is performed by maintaining the temperature at the above-mentioned temperature for 0.5h to 1h; the temperature of the solution treatment is T. β Above 10℃~50℃; Step 2, Gradient Cooling Rate Control: The TC18 rolled tube after solution treatment in Step 1 is first subjected to rapid cooling in a high-temperature stage: rapidly cooled from the β phase region to T at a cooling rate of not less than 0.5℃ / s. β Next, a narrow-range controlled cooling process is performed in the low-temperature stage: the temperature is reduced to room temperature at a cooling rate of 0.03℃ / s to 0.1℃ / s to obtain the heat-treated TC18 pierced-rolled tube; the final temperature of the rapid cooling in the high-temperature stage is T. β Below 30℃~70℃.
2. The gradient cooling rate controlled heat treatment process for TC18 pierced-rolled tubing according to claim 1, characterized in that, The chemical composition of the TC18 rolled tube meets the requirements of TC18 in GB / T 3620.1-2020 "Titanium and Titanium Alloys - Grades and Chemical Compositions".
3. The gradient cooling rate controlled heat treatment process for TC18 pierced rolling tubes according to claim 1, characterized in that, The initial microstructure of the TC18 pierced tube described in step one is as follows: the grain size dispersion is relatively large, with the average size of large-scale grains being close to 200 μm and the average size of small-scale grains being close to 20 μm. The secondary α-phase anomalous enrichment integral is greater than 75%, and it exhibits a submicron needle-like morphology with an average length of less than 1 μm.
4. The gradient cooling rate controlled heat treatment process for TC18 pierced rolling tubes according to claim 1, characterized in that, The grain size dispersion of the TC18 pierced tube after solution treatment in step one is less than ±20μm.
5. The gradient cooling rate controlled heat treatment process for TC18 pierced rolling tubes according to claim 1, characterized in that, The cooling rate of the high-temperature stage rapid cooling described in step two is 0.5℃ / s.
6. The gradient cooling rate controlled heat treatment process for TC18 pierced rolling tubes according to claim 1, characterized in that, The cooling rate of the narrow-range controlled cooling in the low-temperature stage described in step two is 0.06℃ / s to 0.1℃ / s.
7. The gradient cooling rate controlled heat treatment process for TC18 pierced-rolled tubing according to claim 1, characterized in that, The microstructure of the TC18 pierced tube after heat treatment in step two is as follows: β grains are homogenized, grain size dispersion is less than ±30μm, and multi-scale heterogeneous microstructure is reconstructed, wherein the coarse α phase has a size of 10μm~22μm and the fine α phase has a size of less than 1μm.
8. The gradient cooling rate controlled heat treatment process for TC18 pierced-rolled tubing according to claim 1, characterized in that, The TC18 pierced tube after heat treatment in step two has a tensile strength of 1052MPa~1126MPa, a yield strength of 934MPa~1012MPa, and an elongation of 13.0%~15.6%.
Citation Information
Patent Citations
A heat treatment method for TC18 titanium alloy
CN115976441B
Heat treatment process method for consistency of TC18 titanium alloy structure and performance
CN118186325B
Vacuum heat treatment method for ultrahigh-toughness medium-strength high-plasticity TC32 titanium alloy part
CN112680630A
Heat treatment method for TC18 titanium alloy with high fracture toughness
CN115725916A